Students’ Strategies in Translating Humorous Text - Cynthia Felia Chandra (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study aims to find out the problems that students experienced and strategies that students used in translating humorous text. The writer conducted this study using the theory of translation problems and strategies by Baker (2018). This writer conducted this study using a qualitative approach in which she collected and analyzed the data herself. The findings of this study support Baker’s (2018) statement that some of the problems that may appear during translation process are culture-specific concept, the source language concept is not lexicalized in the target language, the source and target language make different distinction in meaning, the target language lacks a specific term (hyponym), differences in expressive meaning, and differences in frequency and purpose of using specific forms. In addition, Text in the source language is translated in several different strategies namely translation by more general word, translation by more neutral or less expressive word, translation by paraphrase using related words, translation by paraphrase using unrelated words, translation using a loan word or loan word plus explanation, and translation by omission. More studies involving other types of humor and other translation theories are recommended to create variations in this field.